KAJIAN PERTUMBUHAN MINAT DAN REALISASI INVESTASI PENANAMAN MODAL ASING (PMA) DAN PENANAMAN MODAL DALAM NEGERI (PMDN) PROVINSI JAWA BARAT (LOKASI DAN SEKTOR USAHA) - Firdaus, Dony Waluya; Widyasastrena, Dimas (Program Studi Akuntansi FPEB UPI, 2016)
Abstract. Investment interest of PMA and PMDN of West Java Province based on location and sector of January - December 2015 at 27 (twenty-seven) regencies/cities reaching a total investment of Rp. 186,491,741,150,000 and total employment of 161,561 people, as well as total projects of 1,540 projects. With the growth of Foreign Investment (PMA) based on the Location of Regency / City and Business Sector of West Java Province reached Rp.135,324,226,250,000 and Domestic Investment Interest (PMDN) of Regency / City and Business Sector of West Java Province reached Rp.51,167,514,900,000. The realization of foreign direct investment (FDI 2015) based on the Location of Regency / City and Business Sector of West Java Province reached Rp.71,733,928,750,000 although in the beginning - the beginning of the year experienced a slowdown, meanwhile. Realization of Domestic Investment (PMDN) based on Location of Regency / City and Business Sector of West Java Province reaches Rp.49,783,024,065,583. Keywords: Interest, Realization; Foreign Investment; Domestic Investment. Abstrak. Minat Investasi PMA dan PMDN Provinsi Jawa Barat berdasarkan lokasi dan sektor Januari – Desember 2015 di 27 (dua puluh tujuh) Kabupaten/Kota mencapai total investasi sebesar Rp. 186,491,741,150,000 dan total penyerapan tenaga kerja sebanyak 161,561 orang, serta total proyek sebanyak 1,540 proyek. Dengan pertumbuhan Minat Penanaman Modal Asing (PMA) berdasarkan Lokasi Kabupaten/Kota dan Sektor Usaha Provinsi Jawa Barat mencapai sebesar Rp.135,324,226,250,000 dan pertumbuhan Minat Penanaman Modal Dalam Negeri (PMDN) Kabupaten/Kota dan Sektor Usaha Provinsi Jawa Barat mencapai sebesar Rp.51,167,514,900,000. Realisasi Penanaman Modal Asing (PMA) 2015 berdasarkan Lokasi Kabupaten/Kota dan Sektor Usaha Provinsi Jawa Barat mencapai Rp.71,733,928,750,000 meskipun di awal – awal tahun mengalami perlambatan, sedangkan. Realisasi Penanaman Modal Dalam Negeri (PMDN) berdasarkan Lokasi Kabupaten/Kota dan Sektor Usaha Provinsi Jawa Barat mencapai mencapai Rp.49,783,024,065,583. Kata Kunci: Minat, Realisasi, Penanaman Modal Asing (PMA), Penanaman Modal Dalam Negeri (PMDN).